2020
DOI: 10.1155/2020/9826084
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adding Neuromuscular Electrical Stimulation with Endurance and Resistance Training on Exercise Capacity and Balance in Patients with Chronic Obstructive Pulmonary Disease: A Randomized Controlled Trial

Abstract: This study investigated the effectiveness of adding neuromuscular electrical stimulation (NMES) to endurance training (ET) and resistance training (RT) on exercise tolerance and balance in COPD patients. 42 patients were assigned randomly to the ET + RT + NMES group (n = 22) or ET + RT group (n = 20). Two training programs were performed including 72 sessions. The center of pressure (CoP) displacement in the mediolateral direction (CoPML), in the anteroposterior direction (CoPAP), and the center of pressure ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Of the 32 1950 randomized clinical trials included in this review, nine were on neuromuscular electrical stimulation alone compared to a control or sham, from which six performed neuromuscular electrical stimulation in clinical setting and three performed in home. Twelve studies were on combined neuromuscular electrical stimulation and conventional rehabilitation (pulmonary rehabilitation or physical therapy) compared to conventional rehabilitation, from which eleven performed neuromuscular electrical stimulation in clinical setting and one performed in home.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 32 1950 randomized clinical trials included in this review, nine were on neuromuscular electrical stimulation alone compared to a control or sham, from which six performed neuromuscular electrical stimulation in clinical setting and three performed in home. Twelve studies were on combined neuromuscular electrical stimulation and conventional rehabilitation (pulmonary rehabilitation or physical therapy) compared to conventional rehabilitation, from which eleven performed neuromuscular electrical stimulation in clinical setting and one performed in home.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, seven studies 22,25,26,34,35,41,50 combined neuromuscular electrical stimulation and conventional rehabilitation versus Conventional Rehabilitation and assessed six minutes walking test as an outcome. The meta-analyses showed (Figure 5) a significant improvement in 6MWT of 34.28 meters (95% CI: 6.84, 61.73, N = 262) for participants in the combined Neuromuscular electrical stimulation and conventional rehabilitation group compared to conventional rehabilitation group.…”
Section: Resultsmentioning
confidence: 99%
“…Amiridis et al [26] have shown that static balance improves 49.4% with NMES training of the tibialis anterior muscle. And Acheche et al [27] showed a 29.3% improvement in balance after applying NMES combined with VMC to the quadriceps and calf muscles. Furthermore, Bondi et al [28] have reported that static balance improved by 30.3% after 8 weeks of application of NMES to the quadriceps and lumbar paraspinal muscles.…”
Section: Discussionmentioning
confidence: 98%
“…This sentence includes cardiovascular problems (hypertension and tachycardia), which are transposable to the 6-minute walking test (6MWT) contraindications. In addition, we expressed the performance in the 6-minute walking test distance (6MWTD) in meters (m), which is the common unit used in many publications ( Acheche et al, 2020 ; ATS, 2002 ; Celli et al, 2016 ; Mekki et al, 2019 ; Holland et al, 2014 ; S. J. Singh et al, 2014 ). The distance walked in meters has similar capacity to predict mortality as the values corrected by using reference equations ( Polkey et al, 2013 ; Puhan et al, 2008 ; S. J. Singh et al, 2014 ), so the 6MWTD is reported in meters.…”
Section: Specific Responsesmentioning
confidence: 99%
“…This sentence includes cardiovascular problems (hypertension and tachycardia), which are transposable to the 6-minute walking test (6MWT) contraindications. In addition, we expressed the performance in the 6-minute walking test distance (6MWTD) in meters (m), which is the common unit used in many publications (Acheche et al, 2020; ATS, 2002; Celli et al, 2016; Mekki et al, 2019; Holland et al, 2014; S. J. Singh et al, 2014).…”
Section: Specific Responsesmentioning
confidence: 99%